ANALISIS FAKTOR EKSPOR KENDARAAN CBU RODA EMPAT DAN ENAM DI INDONESIA TAHUN 2015 – 2019 - Dharma Mahendra, I Putu Sanpala; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.12.TAHUN.2021, 2021)
The industrial sector can develop with government policies and trade between countries. Industrialization plays an important role in improving the quality of human resources and optimally utilizing natural and other resources. To analyze the effect of government policies partially on exports of four- and six-wheeled CBU vehicles in Indonesia from 2015 to 2019. The purpose of this study is to analyze the effect of the rupiah exchange rate against the US dollar partially and simultaneously on exports of four and six-wheel CBU vehicles in Indonesia in 2015. 2015 to 2019. The type of data used is quantitative data, with the data source being secondary data. The analysis technique used in this study uses multiple linear regression analysis techniques. The results of this study indicate that simultaneously government policy variables, exchange rates, and world oil prices have a significant effect on the value of Indonesia's CBU exports in 2014-2019, and partially government policy variables and world oil prices have a positive and significant effect on Indonesia's CBU exports. While the exchange rate variable has a negative and significant effect on Indonesian CBU. This means that if the exchange rate of the rupiah against the dollar increases or the strengthening of the value of the dollar against the rupiah will cause a decrease in the price of exported goods, the value of export goods will also decrease.